The changing context of innovation management: A critique of the relevance of the stage-gate approach to current organizations. (30th August 2022) - Trott, Paul; Baxter, David; Ellwood, Paul; van der Duin, Patrick
Abstract : The stage-gate method was initially developed as a description of the new product development practices within high-performing firms. At its heart the concept is simple: and the flow of activity of a stage-gate includes project action, information generation, analysis and decision. Research has shown that the stage-gate method has been extremely successful in many contexts. The question of whether the approach is suitable for all projects in all situations is a principal faultline within the literature. Proponents argue that adaptations and evolutions of the stage approach enable it to be universally applied. This paper provides a critical review of the literature and we identify chronic limitations of stage-gate when evaluated against contemporary challenges, including VUCA (volatility, uncertainty, complexity and ambiguity), environment, digitization and open innovation. We remain critical about whether these contemporary currents are best approached by yet another reconfiguration of stage-gate building blocks. We argue that high uncertainty (caused by these currents) requires the flexibility to change fundamental elements of a project, including the underlying concept and the target market, which means that stage-gate is not well suited to innovation processes addressing these contemporary challenges. We propose a typology to show its suitability.